Electrolyte based on asymmetric hydrogel, preparation method of electrolyte and application of electrolyte in zinc ion battery
By using an electrolyte based on asymmetric hydrogel in zinc ion batteries, the corrosion and hydrogen evolution reaction problems on the negative electrode side of zinc are solved, and the capacity and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202311267401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
In aqueous zinc ion batteries, due to the interaction between zinc ions and water molecules, corrosion on the negative side of zinc negative electrode, hydrogen evolution side reaction, uncontrollable electrochemical side reactions and branch crystal generation, affecting the capacity and cycle stability of the battery.
The electrolyte based on asymmetric hydrogels is used to prepare gel electrolytes by copolymerizing free radicals containing hydrophobic groups and hydrophilic groups, and combining a hydrophobic molds with one side of hydrophilic side to achieve the reduction of water molecules on the negative side of zinc and the guarantee of water content on the positive side.
It effectively weakens the corrosion of zinc negative electrode and hydrogen evolution reaction, reduces the generation of branch crystals, and improves the capacity and cycle stability of zinc ion batteries.
Smart Images

Figure HDA0004474619130000011 
Figure HDA0004474619130000012 
Figure HDA0004474619130000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and particularly relates to an electrolyte based on an asymmetric hydrogel and application thereof in a zinc ion battery. Background Art
[0002] Aqueous zinc-ion batteries stand out from many batteries because of their suitable redox potential, high theoretical specific capacity, high crustal abundance and low cost, and have great application prospects in future fields such as large-scale energy storage and green energy.
[0003] However, in aqueous zinc-ion batteries, due to the interaction between zinc ions and water molecules, such as the formation of water and zinc ions, the interaction between a large amount of free water and dissolved oxygen molecules in the aqueous electrolyte, corrosion, hydrogen evolution side reactions, uncontrollable electrochemical side reactions, and dendrites generated by uneven deposition of zinc ions will occur on the zinc negative electrode side. The growth of dendrites will lead to the risk of short circuit in zinc-ion batteries. In order to solve the above problems, researchers have prepared a large number of gel electrolytes. Gel electrolytes have a stable three-dimensional network space structure, excellent ion conduction function, and certain viscosity, which improves the interface contact between the zinc negative electrode and the electrolyte. Compared with traditional separators, it can achieve uniform deposition of zinc ions and weaken the formation of dendrites. The hydrogel used in the current study contains a large number of hydrophilic groups, and the water content in the gel is high. The side reactions caused by water molecules still need to be solved. Therefore, it is necessary to reduce the water content in the hydrogel to reduce zinc corrosion, hydrogen evolution, and dendrite formation. For positive electrode materials, the intercalation of hydrogen ions and the lubrication of water molecules play a vital role in improving the utilization rate of positive electrode active materials, increasing the capacity of the battery and achieving the cycle stability of the battery. Therefore, a relatively high water content is required on the positive electrode side. The gel electrolyte currently under study has a symmetrical structure, and too high or too low a water content will limit the capacity and long-term cycle stability of zinc-ion batteries.
[0004] Therefore, it is urgent to develop an asymmetric gel electrolyte that can weaken the active water molecules on the zinc negative electrode while providing sufficient water molecules on the positive electrode side to improve the battery capacity and long-term cycle stability. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention aims to provide an electrolyte based on an asymmetric hydrogel and its application in a zinc ion battery.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0007] The present invention provides a method for preparing an electrolyte based on an asymmetric hydrogel, and the process is as follows:
[0008] The acrylic monomer containing a hydrophobic group, the acrylic monomer containing a hydrophilic group, the diacrylic crosslinking agent, the initiator, the catalyst and the zinc salt are dissolved in water, stirred and mixed at 10-40°C for 5-30 minutes under a protective atmosphere, and then placed in a mold with one side being hydrophobic and the other side being hydrophilic, and polymerized at 20-70°C for 2-36 hours to obtain the asymmetric hydrogel electrolyte. The molar ratio of the acrylic monomer containing a hydrophobic group, the acrylic monomer containing a hydrophilic group and the acrylic salt is (1-50): (50-99), and the molar fraction of the zinc salt in the solution is 0.1-2 mol / L.
[0009] Furthermore, in the above technical solution, the acrylic monomer containing a hydrophobic group is one or a mixture of any proportion of two or more of N-isopropylacrylamide, N,N-diethylacrylamide, and N,N-dimethylacrylamide.
[0010] Furthermore, in the above technical solution, the acrylic monomer containing a hydrophilic group is one or a mixture of any proportion of two or more of acrylamide, acrylic acid, 2-hydroxyethyl acrylate and zinc acrylate.
[0011] Furthermore, in the above technical solution, the diacrylic acid cross-linking agent is N,N'-methylenebisacrylamide, polyethylene glycol diacrylate or tetraethylene glycol diacrylate.
[0012] Furthermore, in the above technical solution, the initiator is ammonium persulfate, potassium persulfate and dibenzoyl peroxide.
[0013] Furthermore, in the above technical solution, the zinc salt is zinc sulfate, zinc carbonate, zinc chloride and zinc trifluoromethanesulfonate.
[0014] Furthermore, in the above technical solution, the polymerization mold with one hydrophobic side and the other hydrophilic side has a hydrophilic side made of glass and a hydrophobic side made of polytetrafluoroethylene or acrylic plate.
[0015] The present invention provides an electrolyte based on an asymmetric hydrogel prepared by the above method.
[0016] The present invention provides application of the electrolyte in a zinc ion battery.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] (1) The present invention prepares a gel electrolyte by free radical copolymerization of an acrylic monomer containing a hydrophilic group and an acrylic monomer containing a hydrophobic group. The preparation method is simple and can be easily expanded on a large scale.
[0019] (2) The present invention prepares an electrolyte based on an asymmetric hydrogel by using a mold with one side being hydrophobic and the other side being hydrophilic. The preparation method is simple and easy, with a wide range of options, and has the possibility of industrial promotion and application.
[0020] (3) The asymmetric hydrogel-based electrolyte prepared by the present invention reduces the water molecules in the zinc negative electrode while ensuring a higher water content on the positive electrode side, thereby improving the capacity and cycle stability of the zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The contact angles of the upper and lower surfaces of the asymmetric hydrogels prepared in Examples 1-3 and Comparative Example 1;
[0022] Figure 2 The contact angles of the upper and lower surfaces of the asymmetric hydrogel prepared in Comparative Example 2-3;
[0023] Figure 3 The full battery with the hydrogel prepared in Example 2 and Comparative Examples 2-3 as electrolyte was tested at 0.5Ag. -1 Cyclic stability test curve under
[0024] Figure 4 The full battery with the hydrogel prepared in Example 2 and Comparative Examples 2-3 as electrolyte was tested at 0.5A g -1 XRD curve of the negative electrode after 100 cycles;
[0025] Figure 5 The full battery with the hydrogel prepared in Example 2 and Comparative Examples 2-3 as electrolyte was tested at 0.5A g -1 XRD curve of the positive electrode after 100 cycles. DETAILED DESCRIPTION
[0026] The following examples further illustrate an asymmetric hydrogel-based electrolyte and its application in zinc ion batteries. The examples are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.
[0027] Example 1
[0028] An electrolyte based on an asymmetric hydrogel and a preparation method thereof, comprising the following steps:
[0029] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate are dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide is 89.97:5:5:0.3. Subsequently, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine are added, and the reaction system is evacuated with inert gas protection. Finally, the system is poured into a mold with one glass and the other polytetrafluoroethylene, and polymerization reaction is carried out at 60°C for 2 hours.
[0030] The prepared asymmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V 10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0031] Example 2
[0032] An electrolyte based on an asymmetric hydrogel and a preparation method thereof, comprising the following steps:
[0033] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate were dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide was 79.97:15:5:0.3. Ammonium persulfate and N,N,N',N'-tetramethylethylenediamine were then added. The reaction system was evacuated with inert gas for protection and finally poured into a mold with one glass and the other polytetrafluoroethylene, and polymerization reaction was carried out at 60°C for 2 hours.
[0034] The prepared asymmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V 10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0035] Example 3
[0036] An electrolyte based on an asymmetric hydrogel and a preparation method thereof, comprising the following steps:
[0037] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate are dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide is 69.97:25:5:0.3. Subsequently, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine are added, and the reaction system is evacuated with inert gas for protection. Finally, the system is poured into a mold with one glass and the other polytetrafluoroethylene, and polymerization reaction is carried out at 60°C for 2 hours.
[0038] The prepared asymmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V 10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0039] Comparative Example 1
[0040] An electrolyte based on an asymmetric hydrogel and a preparation method thereof, comprising the following steps:
[0041] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate were dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide was 94.97:0:5:0.3. Ammonium persulfate and N,N,N',N'-tetramethylethylenediamine were then added. The reaction system was evacuated with an inert gas for protection and finally poured into a mold with one glass and the other polytetrafluoroethylene, and polymerized at 60°C for 2 hours.
[0042] The prepared asymmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V 10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0043] The contact angles of the upper and lower surfaces of the asymmetric hydrogels prepared in Examples 1-3 and Comparative Example 1 are shown in Figure 1 , it can be seen that the contact angle of the upper surface of the asymmetric hydrogel prepared in Examples 1-3 in contact with the polytetrafluoroethylene plate is greater than the contact angle of the lower surface in contact with the glass plate. Comparative Example 1 does not contain the hydrophobic monomer N-isopropylacrylamide, so the contact angle of the upper surface of the hydrogel prepared in Comparative Example 1 in contact with the polytetrafluoroethylene plate is not much different from the contact angle of the lower surface in contact with the glass plate.
[0044] Comparative Example 2
[0045] A symmetrical hydrogel-based electrolyte and a preparation method thereof, comprising the following steps:
[0046] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate were dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide was 79.97:15:5:0.3. Ammonium persulfate and N,N,N',N'-tetramethylethylenediamine were then added, the reaction system was evacuated with inert gas for protection, and finally poured into a mold with polytetrafluoroethylene on both sides, and polymerized at 60°C for 2 hours.
[0047] The prepared symmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0048] Comparative Example 3
[0049] A symmetrical hydrogel-based electrolyte and a preparation method thereof, comprising the following steps:
[0050] Acrylamide, N-isopropylacrylamide, zinc acrylate, N,N'-methylenebisacrylamide and zinc sulfate were dissolved in deionized water, wherein the molar ratio of acrylamide, N-isopropylacrylamide, zinc acrylate and N,N'-methylenebisacrylamide was 79.97:15:5:0.3. Ammonium persulfate and N,N,N',N'-tetramethylethylenediamine were then added, the reaction system was evacuated with inert gas for protection, and finally poured into a mold with two glass surfaces, and polymerized at 60°C for 2 hours.
[0051] The prepared symmetric hydrogel-based electrolyte was combined with zinc foil, (NH4)2V 10 O 25 · Assemble the full battery with 8H2O positive electrode and test the battery performance.
[0052] The contact angles of the symmetrical hydrogels prepared in Comparative Examples 2 and 3 are shown in Figure 2 In Comparative Example 2, both the upper and lower surfaces of the mold are hydrophobic polytetrafluoroethylene plates, and the hydrophobic monomers in the gel have a strong affinity with the polytetrafluoroethylene plates, so the upper and lower contact angles of the symmetrical hydrogel prepared in Comparative Example 2 are relatively large, 49.2° and 52.5°, respectively. In Comparative Example 3, both the upper and lower surfaces of the mold are hydrophilic glass molds, and the hydrophilic monomers acrylamide and zinc acrylate in the gel have a strong affinity with glass, so the upper and lower contact angles of the symmetrical hydrogel prepared in Comparative Example 3 are relatively small, 38.6° and 37.4°, respectively.
[0053] The asymmetric hydrogel electrolyte prepared in Example 2, Comparative Example 2 and Comparative Example 3 and the zinc foil containing (NH4)2V 10 O 25 The charge and discharge results of the full battery assembled with 8H2O positive electrode sheets after 100 cycles at 0.5A / g are shown in Figure 3 It can be seen that the performance of the full battery using the asymmetric hydrogel prepared in Example 2 as the electrolyte is better than the performance of the full battery using the symmetric hydrogel in Comparative Examples 2 and 3 as the electrolyte.
[0054] The hydrogel electrolyte prepared in Example 2, Comparative Example 2 and Comparative Example 3 was mixed with zinc foil, (NH4)2V 10 O 25 The XRD curve of the negative electrode zinc foil of the full battery assembled with 8H2O positive electrode sheet after 100 cycles at 0.5A / g is shown in Figure 4 It can be seen that in Example 2 and Comparative Example 2, the hydrophobic surface of the asymmetric gel and the hydrophobic surface of the symmetric gel contact the zinc foil, the active water content is low, and almost no by-product (Zn(OH)2)3(ZnSO4)(H2O)5 is generated. In Comparative Example 3, the hydrophilic surface of the symmetric gel contacts the zinc foil, and the active water content is very high, so a large amount of by-product (Zn(OH)2)3(ZnSO4)(H2O)5 is generated.
[0055] The asymmetric hydrogel electrolyte prepared in Example 2, Comparative Example 2 and Comparative Example 3 and the zinc foil containing (NH4)2V 10 O 25 The full battery assembled with 8H2O positive electrode contains (NH4)2V after 100 cycles at 0.5A / g 10 O 25 ·The XRD curve of the positive electrode of 8H2O can be found in Figure 5 It can be seen that the hydrophilic surface of the asymmetric gel and the hydrophilic surface of the symmetric gel contact the positive electrode sheet in Example 2 and Comparative Example 3, there are enough water molecules on the positive electrode side, and the positive electrode material is effectively utilized through the co-intercalation of zinc ions and hydrogen ions in the positive electrode. Therefore, almost no byproduct Zn3(OH)2(V2O7)(H2O)2 is generated in the positive electrode sheet in Example 2 and Comparative Example 3. In Comparative Example 2, the hydrophobic surface in the symmetric gel contacts the positive electrode sheet, and a large amount of byproduct Zn3(OH)2(V2O7)(H2O)2 is generated after the cycle.
Claims
1. A method for preparing an electrolyte based on an asymmetric hydrogel, characterized in that: An acrylic monomer containing a hydrophobic group, an acrylic monomer containing a hydrophilic group, a diacrylic crosslinking agent, an initiator, a catalyst and a zinc salt are dissolved in water, stirred and mixed at 10-40° C. for 5-30 minutes under a protective atmosphere, and then placed in a mold with one side being hydrophobic and the other side being hydrophilic, and polymerized at 20-70° C. for 2-36 hours to obtain the asymmetric hydrogel electrolyte; the molar ratio of the acrylic monomer containing a hydrophobic group to the acrylic monomer containing a hydrophilic group is (1-50):(50-99), and the molar fraction of the zinc salt in the solution is 0.1-2 mol / L.
2. The preparation method according to claim 1, characterized in that: The acrylic monomer containing a hydrophobic group is one of N-isopropyl acrylamide, N,N-diethyl acrylamide, and N,N-dimethyl acrylamide, or a mixture of two or more of them in any proportion.
3. The preparation method according to claim 1, characterized in that: The acrylic monomer containing a hydrophilic group is one or a mixture of two or more of acrylamide, acrylic acid, 2-hydroxyethyl acrylate and zinc acrylate in any proportion.
4. The preparation method according to claim 1, characterized in that: The diacrylic acid cross-linking agent is N,N'-methylenebisacrylamide, polyethylene glycol diacrylate or tetraethylene glycol diacrylate.
5. The preparation method according to claim 1, characterized in that: The initiator is ammonium persulfate, potassium persulfate or dibenzoyl peroxide.
6. The preparation method according to claim 1, characterized in that: The zinc salts are zinc sulfate, zinc carbonate, zinc chloride and zinc trifluoromethanesulfonate.
7. The preparation method according to claim 1, characterized in that: The polymer mold with one hydrophobic side and the other hydrophilic side has a hydrophilic side made of glass and a hydrophobic side made of polytetrafluoroethylene or an acrylic plate.
8. An asymmetric hydrogel-based electrolyte prepared by the method of any one of claims 1 to 7.
9. Use of the electrolyte according to claim 8 in a zinc ion battery.
Citation Information
Patent Citations
Multifunctional gel polymer electrolyte and preparation method thereof
CN115894788A
Hydrogel and method for producing same
WO2017051734A1
Polyanionic zinc salt hydrogel electrolyte and zinc battery system
WO2022057160A1